Beautiful ugly ebook A novel. - Feeney, Alice (2025)
INSTANT NEW YORK TIMES BESTSELLER "Her best book yet." — Harlan Coben The million-copy bestselling Queen of Twists Alice Feeney returns with a gripping and deliciously dark thriller about marriage. . . . . . and revenge. Author Grady Green is having the worst best day of his life. Grady calls his wife to share some exciting news as she is driving home. He hears Abby slam on the brakes, get out of the car, then nothing. When he eventually finds her car by the cliff edge the headlights are on, the driver door is open, her phone is still there. . . but his wife has disappeared. A year later, Grady is still overcome with grief and desperate to know what happened to Abby. He can't sleep, and he can't write, so he travels to a tiny Scottish island to try to get his life back on track. Then he sees the impossible – a woman who looks exactly like his missing wife. Wives think their husbands will change but they don't. Husbands think their wives won't change but they do. "Magnetic and jaw-dropping." —Mary Kubica, bestselling author "Unforgettable." —Chris Whitaker, bestselling author